QoE in multi-service multi-agent networks. (26th January 2010) - Liberal, Fidel; Ferro, Armando; Koumaras, Harilaos; Kourtis, Anastasios; Sun, Lingfen; Ifeachor, Emmanuel
The growth of emerging multimedia applications with different quality requirements has made the objective network QoS (NQoS) to be commonly considered as an inadequate metric for quality assessment in telecommunication services, being the quality of experience (QoE) concept the most predominant alternative. However, most QoE-related research studies are service-specific, not easily expandable to other multimedia services and unsuitable for tuning up network management procedures. Instead, we propose an integrated QoE management model and a calculus process that estimates final user-satisfaction over multi-service scenarios and identifies those elements that have a greater impact on users' QoE. In order to evaluate this impact, new VoIP and video perception assessment methods were developed, while state-of-the-art methods were used for web and online game services. The effectiveness of the model is demonstrated by applying a stepwise multiple linear regression method to identify both subjective and objective bottlenecks in the network.